MEMAHAMI HERMENEUTIKA DALAM MENGKAJI TEKS - Rini Fitria (JURNAL ILMIAH SYI'AR, 2016)
This paper contains about how to understand that a critical hermeutika science initially began studies toward understanding the philosophy of communication science or broadcast Islamic communication to understand texts. Hermeutika theoretical, philosophical hermeneutics and critical hermeneutics is the Science of how to interpret the meaning contain in the texts with the initiators study o, the reader and the contextin which it.